Patient-Specific or Conventional Instrumentations: A Meta-analysis of Randomized Controlled Trials. (10th March 2020) - Lin, Yipeng; Cai, Wufeng; Xu, Baoyun; Li, Jian; Yang, Yuan; Pan, Xuelin; Fu, Weili
Abstract : Objective . To conduct a meta-analysis of randomized controlled trials (RCTs) to compare knee arthroplasty with patient-specific instrumentation (PSI) with the conventional instrumentation (CI). Methods . RCTs were selected in PubMed and Embase from 2012 to 2018. Key data extracted included malalignment of mechanical axis, blood loss, surgical time, Oxford Knee Score (OKS), Knee Society Score (KSS), length of stay, and complications. Subgroup analysis was also performed regarding different PSI systems and different image processing methods. Results . 29 RCTs with 2487 knees were eligible for the meta-analysis. Results showed that PSI did not improve the alignment of the mechanical axis compared with CI, but MRI-based PSI and Visionaire-specific PSI decrease the risk of malalignment significantly (P = 0.04 and P = 0.003, respectively). PSI reduced operative time (P = 0.03 ) and blood loss (P = 0.002 ) and improve the KSS (P = 0.02 ) compared with CI, but for CT-based PSI, the difference of operative time becomes insignificant. PSI showed no significant difference with CI regarding risk of complication, length of stay in hospital, and functional outcomes of OKS. Conclusion . PSI reduced the blood loss and improved KSS. MRI-based PSI reduced operative time and risk of malalignment of mechanical axis compared with CT-based PSI. Moreover, Visionaire-specific PSI achieves better alignment result of the mechanical axis than other systems.